1995
DOI: 10.1007/bf01816946
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor is cardioprotective in ischemia-reperfusion injury

Abstract: To examine whether basic fibroblast growth factor (bFGF) administered to the heart by perfusion can improve cardiac resistance to injury we employed an isolated rat heart model of ischemia-reperfusion injury and determined the extent of functional recovery in bFGF-treated and control hearts. Global ischemia was simulated by interruption of flow for 60 min. Recovery of developed force of contraction (DF), recorded after reestablishment of flow for 30 min, reached 63.8 +/- 1.5% and 96.5 +/- 3.5% of preischemic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…Interestingly, FGF2 LMWKO mouse hearts, in which only the FGF2 HMW isoforms are present, had a percent recovery of post-ischemic contractile function similar to mice deficient in all LMW and HMW isoforms ( Figure 5). This observation suggests that the LMW isoform is responsible for protecting the heart from myocardial dysfunction which is consistent with that reported by the Kardami group [9,14]. A question remains as to what roles, if any, do the HMW isoforms of FGF2 have in cardioprotection and ischemia-reperfusion injury.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Interestingly, FGF2 LMWKO mouse hearts, in which only the FGF2 HMW isoforms are present, had a percent recovery of post-ischemic contractile function similar to mice deficient in all LMW and HMW isoforms ( Figure 5). This observation suggests that the LMW isoform is responsible for protecting the heart from myocardial dysfunction which is consistent with that reported by the Kardami group [9,14]. A question remains as to what roles, if any, do the HMW isoforms of FGF2 have in cardioprotection and ischemia-reperfusion injury.…”
Section: Discussionsupporting
confidence: 89%
“…Although FGF2 LMW and HMW isoforms have different biological functions in several in vitro studies, the question remains as to the role of specific FGF2 isoform(s) in I/R injury and cardioprotection. Kardami and colleagues demonstrated that treatment with the FGF2 LMW isoform improved cell survival and functional recovery in the ischemic rat heart [14] and also that overexpression of the FGF2 LMW isoform in mice reduced cardiomyocyte damage [9]. In the present study, the role of FGF2 LMW isoform in I/R injury was elucidated by subjecting novel mouse models to I/R injury.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, Padua et al reported that, in the rat, damage from an injury to the myocardial tissues of a bFGF-treated heart was less than in a control heart, and they suggested that bFGF has a direct cardioprotective effect. 40 Taking all the results together, bFGF may be correlated with the wound healing processes in injured myocardial tissue.…”
Section: Bfgf and Vegf Actions On The Injury Of Myocardial Tissuesmentioning
confidence: 99%